Pengembangan dan Implementasi Buku Teks Berorientasi Project Based Learning (PjBL) untuk Meningkatkan Kreativitas Mahasiswa - Sani Safitri; Fatimah, Siti; Alfiandra (Universitas Pendidikan Ganesha, 2024)
The learning process that takes place so far has yet to maximize and encourage students' thinking skills and learning creativity. This can be seen from the learning process of social studies education courses, which tends to use approaches that do not maximize the development of student creativity. This study aims to create teaching materials in the form of teaching books for social studies education courses oriented to project-based learning and see the potential effect on student creativity. The subjects in this study amounted to 45 students and involved three types of experts: material experts, design experts and linguists. This type of research is development research, with the development model used as the ASSURE model modified with formative evaluation from Tessmer. The data collection methods used in this research are tests, questionnaires, observation techniques, and interviews using instruments in the form of questionnaire sheets and tests with essay forms. After collecting the data, they were analyzed using descriptive qualitative and quantitative data analysis methods like n-gain. The main results of this study indicate that the project-based Learning-oriented textbook products developed meet the criteria of validity, practicality, and effectiveness. So, the product of the Project-based learning-oriented Social Studies Education course textbook developed is valid, practical, and effective in increasing student creativity. This research makes a meaningful contribution to the field of education, especially in developing project-oriented teaching materials.